Aspects of the thermal ecology of six species of carcass beetles in South Africa - Midgley, John Mark (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2008)
The forensic application of entomology is well known, but it is generally a field which concentrates on Diptera. Many Coleoptera also have forensic application, but are generally neglected by forensic entomology researchers. Necrophilic Coleoptera are diverse and therefore have application in estimating Post-Mortem Interval (PMI) by community composition, but they are also valuable in estimating PMI by development. In addition, Coleoptera are more common in stored product cases. Six species of forensically important Coleoptera were studied, three from the family Dermestidae (Dermestes haemorrhoidalis, D. maculatus and D. peruvianus) and three from the family Silphidae (Silpha punctulata, Thanatophilus micans and T. mutilatus). The effect of killing method and storage time on larval length was investigated in T. micans. Coleopteran larvae were shown not to behave in the same way as dipteran larvae. In contrast to dipteran larvae, it is recommended that coleopteran larvae be killed using ethanol. A development model is presented for T. micans. This represents the first statistically robust development model for forensically important Coleoptera, and the first development model for forensically important Silphidae. The model offers a method of estimating PMI which can be used once Diptera are no longer present on a corpse. Upper lethal temperature limits for four species of carcass beetle were determined. A comparison between species shows distinct differentiation between families and species. This differentiation accounts for microhabitat differences which these species show on carcasses. Bioclimatic models for the six species showed contrasting distributions, with both widespread and localised species. These models allow forensic investigators to assess whether the absence of a species from a corpse is forensically significant, or a result of the species distributions. Moisture-related variables were shown to be more important in predicting species distributions than temperature at a regional scale. Forensic entomology standards can be adjusted based on the findings of this study. Length was again shown to be an inferior measurement of larval age. Coleopteran development has been shown to be useful, and should be given greater consideration in future work. T. micans has been shown to be capable of locating and ovipositing on carcasses promptly after death, making it a good forensic indicator. Further work is needed for the full potential of necrophilic Coleoptera to be realised.
Keywords: Forensic entomology; Diptera -- South Africa; Beetles -- South Africa; Burying beetles; Burying beetles -- South Africa; Beetles -- Effect of temperature on